East Door of Sun Temple, Konark in Odisha - Temples of India Project Team (Jio Institute, 2024)
East door to Jagamohan, Sun Temple, Konark, Odisha, India, Ganga period, reign of Narasimhadeva I, 1238-58 CE. Image courtesy: Prof. Chedha Tingsanchali.